Cognitive Approach to Synonymic Relationship in Terminology - Khujakulov, Sunnatullo Anvar ugli (Indonesian Journal of Innovation Studies, 2022)
The complex and least studied aspects of the study of terms include questions of their systemic organization at the level of lexico-semantic paradigmatics. An important problem that requires a detailed study on the material of various term systems is the implementation of the semantic process of synonymy in terminology. Based on this, the article reveals the content of the term "terminological synonymy". The main attention of the author is drawn to the generalization of theoretical views on the essence of the phenomenon of synonymy in terminology. The study analyzes the cognitive approach to synonymic relationship in terminology, including the interpretation of the concepts of "synonym", "doublet" and "variant", also offers its own understanding of these concepts.